The Role of Umbilical Cord Blood Concentration of IGF-I, IGF-II, Leptin, Adiponectin, Ghrelin, Resistin, and Visfatin in Fetal Growth - Yalinbas, Emine Esin; Binay, Cigdem; Simsek, Enver; Aksit, Mehmet Arif (American Journal of Perinatology, 2019)
Objective Herein, we measured the concentration of insulinlike growth factor I (IGF-I), IGF-II, leptin, adiponectin, ghrelin, resistin, and visfatin in the umbilical cord blood of newborns categorized as “small for gestational age” (SGA), “appropriate for gestational age” (AGA), and “large for gestational age” (LGA). Our aim was to elucidate the link between the levels of these proteins and fetal growth.Study Design A total of 96 term infants were included and categorized into three weight categories. Their venous cord blood samples were collected to measure the levels of IGF-I, IGF-II, leptin, adiponectin, ghrelin, resistin, and visfatin.Results IGF-I, visfatin, and leptin levels showed significant differences among the groups. Pairwise comparisons showed that adiponectin (p = 0.023), resistin (p = 0.025), and ghrelin (p = 0.005) levels were significantly lower in the SGA group than in the LGA group. Correlation analyses showed a strong association of IGF-1, IGF-II, and leptin levels with birth weight (r = 0.644, p < 0.001; r = 0.441, p < 0.001; and r = 0.404, p < 0.001, respectively).Conclusion SGA newborns showed a significantly higher visfatin concentration and lower ghrelin, leptin, resistin, and adiponectin levels than the AGA and LGA newborns did.
Keywords: fetal growth; visfatin; ghrelin; leptin; resistin